VD_FINDINFO Arrêt / 2014 / 748 vom 6. November 2014 - VD Tribunal cantonal (2014)
RESTITUTIONEN GÉNÉRAL, REMISE DE LA PRESTATION, COMPENSATION DE CRÉANCES | 94 LACI, 95 al. 1 LACI, 95 al. 1bis LACI, 25 LPGA